Menggugah Realitas Sosial: Kajian Sosiologi Sastra dalam Novel Laskar Pelangi Sebagai Representasi Ketidakmerataan Pendidikan Indonesia - Rifqi Nandana Mahardika; Hanuun Dhiyaa Putri Ari; Amanda Ivani; Fora Shaffilia Hakik; Qurrota Ayu Neina; Tommi Yuniawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The persistence of educational inequality in Indonesia remains evident today. This situation parallels the depiction in Andrea Hirata’s 2005 novel Laskar Pelangi, indicating that the social critique offered by the work has yet to effect widespread change. This study uses a sociological-literary approach to analyze representations of educational inequity in Indonesia as portrayed in Laskar Pelangi. The research uses a descriptive qualitative method, treating novel excerpts as primary and reports as secondary data. Thematic analysis is applied, and data validity is ensured through triangulation within a cross-sectional timeframe. Based on eight data points presented in the results table, the discussion details how the novel illustrates disparities in educational access across six dimensions: infrastructure, teacher availability, facility provision, student distribution, assessment processes, and talent development. These findings reveal the social function of literature as a form of social criticism that can raise public awareness and inform policy initiatives aimed at achieving more equitable education in Indonesia.